The SNARE Machinery in Mast Cell Secretion - Lorentz, Axel; Baumann, Anja; Vitte, Joana; Blank, Ulrich (Frontiers in Immunology, 2012)
Mast cells are known as inflammatory cells which exert their functions in allergic and anaphylactic reactions by secretion of numerous inflammatory mediators. During an allergic response, the high-affinity IgE receptor, FcεRI, becomes cross-linked by receptor-bound IgE and antigen resulting in immediate release of pre-synthesized mediators – stored in granules – as well as in de novo synthesis of various mediators like cytokines and chemokines. Soluble N-ethylmaleimide-Sensitive Factor (NSF) Attachment Protein (SNAP) Receptors (SNARE) proteins were found to play a central role in regulating membrane fusion events during exocytosis. In addition, several accessory regulators like Munc13, Munc18, Rab GTPases, SCAMPs, complexins or synaptotagmins were found to be involved in membrane fusion. In this review we summarize our current knowledge about the SNARE machinery and its mechanism of action in mast cell secretion.